Tamsulosin versus nifedipin in medical expulsive therapy for distal ureteral stones and the predictive value of Hounsfield unit in stone expulsion. (November 2014) - Balci, Melih; Tuncel, Altug; Aydin, Omur; Aslan, Yilmaz; Guzel, Ozer; Toprak, Ugur; Polat, Fazli; Atan, Ali
Abstract We evaluated the efficacy of tamsulosin and nifedipine in medical expulsive therapy (MET) in patients with distal ureteral stone. In addition, we tried to determine the predictive value of Hounsfield Unit (HU) of the stone in the success of MET. A total of 75 patients with a distal ureteral stone of 5–10 mm diameter were randomly divided into three groups. Group 1 (n = 25) received tamsulosin 0.4 mg/d; group 2 (n = 25) received nifedipine 10 mg/day p.o and group 3 (n = 25) received diclofenac sodium 50 mg p.o. when required. At the beginning of each treatment, the HU of the stone was also measured using a non-contrast computerized tomography in all the patients. The results were evaluated at week four. The mean age of the patients was 36.8 (range, 16–68) years. Stone expulsion was observed in 19 (76%) patients in group 1, 16 (64%) patients in group 2 and 9 (36%) patients in group 3 (pgroup1-3 = 0.004, pgroup2-3 = 0.048 and pgroup1-2 = 0.355). The mean expulsion time was 9, 9.1 and 10.3 d, respectively (pgroup1-3 < 0.001, pgroup2-3 < 0.001 and pgroup1-2 = 0.619). The mean diclofenac sodium dose per patient was 544, 602 and 1408 mg in groups 1, 2 and 3, respectively (pgroup1-3 < 0.001, pgroup2-3 < 0.001 and pgroup1-2 = 0.977). The mean HU of the stone in patients with and without a successful MET was 363 and 389, respectively (p = 0.462). Our results showed that MET with both nifedipine and tamsulosin provided a similar increase in the expulsion rate for distal ureteral stones. HU does not seem to be a predictive parameter for stone expulsion.